Hormonal drugs for the treatment of endometriosis. (December 2022) - Capezzuoli, Tommaso; Rossi, Margherita; La Torre, Francesco; Vannuccini, Silvia; Petraglia, Felice
Abstract: In the past, the primary approach for the treatment of endometriosis was represented by surgery; however, after the introduction of non-invasive diagnosis of endometriosis with the development of imaging technologies, medical treatment became the preferred approach, particularly in young patients. Hormonal drugs, by blocking menstruation, are the most effective for the treatment of endometriosis-related pain, independently of phenotype (ovarian, deep, or superficial endometriosis). Gonadotropin-releasing hormone analogs and oral antagonists act on hypothalamus-pituitary-ovary axis inducing iatrogenic menopause, thus reducing dysmenorrhea and all pain symptoms. The side effects, such as hot flushes and bone loss, may be reduced by an add-back therapy. However, the cost in terms of women's health remains high in view of a long-term treatment. Progestins are considered the first-line treatment, highly effective, and with reduced side effects. In addition to the well-known and largely used Norethisterone acetate and Medroxyprogesterone acetate, recently Dienogest has become one of the most used drugs in all endometriosis phenotypes for long-term treatment. Besides, Intrauterine levornogestrel or subcutaneous etonogestrel are valid alternative for long-term treatment.